PELATIHAN PENGOLAHAN DAN PEMASARAN PRODUK BERBASIS SINGKONG DI DESA GIRI TEMBESI - Aprilla, Diah Mitha; Maulida, Sylmi; Putri, Indah Annisa; Fitriana, Nur Fadila; Julianti, Nova; Korniawan, Ojik Danang; Wahyudi, Reza Izam; Agustina, Rizki; Firdaus, Rizqi Rohmatul; Walid, Walid; Buhari, Nurliah (Universitas Mataram, 2024)
Giri Tembesi Village is a village located in Gerung District, West Lombok Regency, West Nusa Tenggara. This village consists of 7 hamlets spread across its territory. This village is also the southernmost tip of Gerung District. This village was originally part of Banyu Urip Village, Gerung District, West Lombok Regency, West Nusa Tenggara and was expanded in 2015. The population of Giri Tembesi Village based on 2022 data is 4431 people, with 1483 heads of families. Based on the results of observations and interviews conducted with the Village Government and the community regarding the Potential of Giri Tembesi Village, there is data that the community has a rice field area of around 183.2 Ha/m2 with agricultural land owners around 850 families. With Potential In this village, there are many people who work on agricultural products to sell and process them into products that have sales value such as mustofa cassava and potato donuts. However, limited public knowledge regarding the development of processed cassava-based products, and the lack of good processing techniques and a small market share hamper the development of the potential of the agricultural sector in the village. Therefore, efforts need to be made to improve the quality of cassava production and improve the processing process so that it can have a positive impact on the economic development and welfare of the people of Giri Tembesi Village. The main work program in implementing this KKN includes counseling on the creativity of processed cassava products, making processed foods, and marketing processed cassava products in Giri Tembesi Village.